Low-Frequency Shear Parameters Viscoelastic Relaxation Process - Adiyasuren, P; Damdinov, BB; Tsend-Ayush, A; Norgov, E (Proceedings of the Mongolian Academy of Sciences, 2011)
An experimental study of the shear parameters of viscoelastic liquids is carried out by the acoustic resonance method based on the changes in the natural frequency and Q factor of a piezoelectric quartz resonator. The liquid to be studied is placed between a stationary quartz strap and the piezoelectric quartz crystal vibrating at the resonance frequency. For a set of drilling mud, the values of the real and imaginary shear module are obtained at a frequency of 74 kHz. The measurements are performed with a liquid layer thickness much smaller than the shear wavelength. It is shown that the shear modulus decreases with increasing strain amplitude. A hole-cluster model based on the Isakovich- Chaban nonlocal diffusion theory is proposed for explaining the low-frequency viscoelastic relaxation process. DOI: http://dx.doi.org/10.5564/pmas.v0i4.46 Proceedings of the Mongolian Academy of Sciences 2009 No 4 pp.53-58